Students' Capability in Answering Multiple Choice Question of Reading Passage At Ninth Grade of SMP Muhammadiyah 4 Surakarta in 2011/2012 Academic Year - MAGFUR, ARBI (2012)
The purposes of this study are describing (1) the students' capability in answering multiple choice question of reading passage at the ninth grade of SMP Muhammadiyah 4 Surakarta in 2011/2012, (2) the problem faced by the students, and (3) the causes of the problem faced by the students. The study was done in SMP Muhammadiyah 4 Surakarta. As the sample, the writer takes 32 students at class IX B. The writer conducts treatment to the students in the form of the test. The type of test is multiple choices with four options and consists of 50 items. After collecting the data and analyzing them by using the formula, the writer describes the result of the study. The writer finds that the capability of the students in answering multiple choice question of reading passage can be divided into three levels mastery, they are 7 students who get poor level (21, 88 %), 15 students who get fair level (46, 87% ), and 10 students who get good level (31, 25 %). The problems faced by the students in answering multiple choice question of reading passage are (1) in answering directly and indirectly answered details questions and (2) vocabulary questions. The causes of the problems faced by the students in answering multiple choice question of reading passage are (1) the students are lack in the mastery vocabulary, sentence's structure, and the ideas of a text or the context of reading passage. (2) The students do not have habit to develop their reading skill. (3) The students do not know the effectiveness strategies to comprehend the reading passage and to answer multiple choice question of reading passage. (4) In the teaching reading the teacher is still less giving variation strategies in answering multiple choice questions and comprehending reading passage for the students. In conclusion the students' capability in answering multiple choice question of reading passage is fair.